Strategi Public Relations Chiki Twist dalam Meningkatkan Brand Awareness - Dense, Aldila; Hadi, A. Sigit Pramono (Interaktif : Jurnal Ilmu-Ilmu Sosial, 2021)
Chiki has been in Indonesia since 1980, had suspended for 8 years in the 2010 era. In 2021, Chiki released a snack innovation called Chiki Twist. This extruded snack made of corn flour requires a public relations (PR) strategy to increase brand awareness. By communicating #PlayTheCircleofFun, Chiki Twist communicates that Chiki Twist is a playmate among the daily activities by its target market. The purpose of this research is to find out how the PR strategy of Chiki Twist as a new brand is to increase brand awareness. The research method is descriptive qualitative with data collection techniques, in-depth interviews and focus group discussions (FGD). The results of the study stated that Chiki Twist carried out both offline and online PR strategies. The PR strategies implemented are sampling, bundling, and education. While the PR strategy is online (digital), Chiki Twist focuses on digital assets on Instagram, TikTok, YouTube, and Twitter. In this digital asset, Chiki Twist communicates value and positioning in the form of content. Other support that is run on digital is also using media ads, micro influencers, macro influencers, to increase awareness. Consumers perceived the message communicated by Chiki Twist, the results state that the PR strategy to increase awareness which is conducted by Chiki Twist has been successful.